Photochemical polymerization of thiophene derivatives in aqueous solution - Piletsky, Sergey A.; Piletska, Elena V.; Karim, K.; Davis, Frank; Higson, Seamus P. J.; Turner, Anthony P. F. (Royal Society of Chemistry, 2004)
A novel method of photochemical polymerization of thiophene derivatives in aqueous solution catalyzed by potassium dichromate and initiated by illumination is described.